2014
DOI: 10.1002/2014jf003117
|View full text |Cite
|
Sign up to set email alerts
|

InSAR measurements of compaction and subsidence in the Ganges‐Brahmaputra Delta, Bangladesh

Abstract: Many of the world′s largest river deltas are sinking due to sediment loading, compaction, and tectonics but also recently because of groundwater extraction, hydrocarbon extraction, and reduced aggradation. Little is known, however, about the full spatial variability of subsidence rates in complex delta systems. This study reconstructs subsidence rates in the eastern portion of the Ganges-Brahmaputra Delta (GBD), Bangladesh, covering more than 10,000 km 2 at a high spatial resolution of 100 m. The map was produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 43 publications
6
89
4
Order By: Relevance
“…4e). These CR values are in the range of what it is observed for modern deltas: 1-2 mm yr −1 for the Fraser, Nile and Mississippi deltas (Mazzotti et al, 2009;Wöppelmann et al, 2013;Törnqvist et al, 2008) and up to 15-18 mm yr −1 in some parts of the Po and Ganges-Brahmaputra deltas (Teatini et al, 2011;Higgins et al, 2014). Contrary to those studies (except for the Po delta that seems to behave similarly), the CR increases until the coastline.…”
Section: Deltas and Sediment Compactioncontrasting
confidence: 49%
See 1 more Smart Citation
“…4e). These CR values are in the range of what it is observed for modern deltas: 1-2 mm yr −1 for the Fraser, Nile and Mississippi deltas (Mazzotti et al, 2009;Wöppelmann et al, 2013;Törnqvist et al, 2008) and up to 15-18 mm yr −1 in some parts of the Po and Ganges-Brahmaputra deltas (Teatini et al, 2011;Higgins et al, 2014). Contrary to those studies (except for the Po delta that seems to behave similarly), the CR increases until the coastline.…”
Section: Deltas and Sediment Compactioncontrasting
confidence: 49%
“…Indeed, many of the world's largest river deltas are primarily sinking under the effect of sediment compaction (Syvitski et al, 2009). Examples include the Fraser river delta in Western Canada (Mazzotti et al, 2009), the Mississippi delta in the USA (Törnqvist et al, 2008), the Po delta in Italy (Teatini et al, 2011) or the Ganges-Brahmaputra delta in Bangladesh (Higgins et al, 2014).…”
Section: Origin Of the Subsidencementioning
confidence: 99%
“…Sediment accumulation in this poldered area also offsets regional, yet locally heterogeneous, subsidence rates of up to 1.8 cm yr -1 (c.f., Higgins et al, 2014;Brown and Nicholls, 2015). If our sedimentation results are considered alongside relative sea level rise and subsidence rates independently, and 2012 is assumed to represent an average flood year, it appears that mean annual accumulation is more than sufficient for reducing the risk of coastal flooding in the central lower Bengal Delta.…”
Section: Sediment Subsidence and Sea Level Risementioning
confidence: 99%
“…These values are due to climate change alone, but subsidence will increase the rise in sea level experienced on the ground; this issue was raised by Milliman et a.l. 1 in 1989, when little data was available to quantify the effect, and studies since 2000 have confirmed that the coastal areas of the GBM delta are undergoing land subsidence 5,6 . Syvitski et al 7 argued that the entire GBM delta is sinking at an alarming rate.…”
Section: Introductionmentioning
confidence: 99%